Analysis of the role of spiritual and corporeal geometry in the architecture of Soltaniyeh dome - Sware Amirashayeri; Lida Balilan Asl; Dariush Satarzadeh; Farah Habib (هنر اسلامی, 2022)
Geometry has a special place in Iranian architecture (both pre-Islamic and post-Islamic). Basically, the purpose of using geometry in architecture was to develop and expand the forms and manifestations derived from nature to promote matter and express the principles and beliefs that were considered sacred in their essence in each period. In the period of Iranian-Islamic architecture, the main goal is perfection (the absolute sole of existence). Because geometry can be effective as a tool to improve the quality of the building and understand the meaning and concept of architecture, The aim of this study is to investigate the role of spiritual geometry (abstract world) and corporeal (material world) as a connection point and interface between meaning and body in the architecture of Soltaniyeh dome. The method of the present study is descriptive-analytical. A set of characteristics based on documentary and library studies as well as analyzes for geometry, in two spiritual parts, including symbol and corporeal geometry, including quantitative and qualitative aspects to investigate its role in the architecture of Soltaniyeh dome Is considered. The results of the research show that the spiritual geometry in the structure of the dome using the codes (numbers) and symbols (shapes) creates the most expression in the physical-spatial part. Also, the existence of laws and characteristics (qualitative and quantitative aspects (sizes)) of corporeal geometry, including symmetry, balance, coordination, etc., has caused the materials used in corporeal and material aspects to be improved and the ability to carry meanings, Increase in its corporation.